Mastering myths and wandering wallflowers : botanical illustrations, gardens and the "mastery of nature" - Du Toit, Victoria (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Visual Arts. Illustration))--University of Stellenbosch, 2009 .